Assessment of the Environmental Friendliness of Fixed Lift Net Fishing Gear in Rebo Waters, Bangka Belitung Islands Province - Zerli Selvika; Dareen Nadya Rema; Silvy Syukhriani; Ali Muqsit (International Journal Multidisciplinary Science, 2026)
Lift net is a fishing gear widely used by coastal fishers in Rebo Waters, Bangka Belitung Province, Indonesia; therefore, its level of environmental friendliness needs to be assessed to support sustainable capture fisheries management. This study aimed to evaluate the environmental friendliness of bagan tancap based on technical and biological–environmental aspects. A descriptive approach with a scoring system was applied to several criteria, including operational safety, energy consumption, ghost fishing potential, catch selectivity, discard handling, interactions with protected species, and impacts on aquatic habitats. The results showed that bagan tancap obtained a total score of 26 out of a maximum score of 30, with an Environmental Friendliness Index (EFI) of 86.67%, indicating that this fishing gear is highly environmentally friendly. However, catch selectivity remained low due to the use of light attraction, which resulted in mixed catches. Keywords: Capture Fisheries, Environmental Friendliness, Fixed Lift Net, Rebo Waters.